GENERALLY RECOGNIZED PRINCIPLES OF INTERNATIONAL LAW AND EMERGING CHALLENGES: THE CASE OF CONTEMPORARY MEDICAL TECHNOLOGIES - Viktorovna Bobrova, Yulia; Evgenievna Gulyaeva, Elena; Torres Manrique, Jorge Isaac (REVISTA ESMAT, 2025)
New medical technologies are advancing unstoppably, specifically 4P medicine. However, this rapid progress causes friction with the principles of international law. The authors propose that, due to the immutability of general principles of law, it is essential that these principles be updated so that they can be brought into line with the new reality and advances in 4P medicine.